2011
DOI: 10.1021/jp202578s
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of SDS/CTAB Catanionic Surfactant Mixture in Aqueous Solution and at the Air/Water Interface

Abstract: Herein, we report the aggregation behavior of catanionic mixtures of the anionic surfactant sodium dodecyl sulfate (SDS) and the cationic surfactant cetyltrimethylammonium bromide (CTAB) in solution and at the air/water interface obtained by the Langmuir-Blodgett (LB) technique. We employed Fourier transform infrared spectroscopy, in situ phase-contrast inverted microscopy, scanning electron microscopy, and atomic force microscopy to characterize the systems in solution, at the air/water interface, and in LB f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…Vesicles spontaneously formed in the mixtures of two single-tailed surfactants with opposite charge have been widely observed1484950515253. It is known that lipids with double hydrocarbon chains such as phospholipids have a tendency to form vesicles, i.e., liposomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vesicles spontaneously formed in the mixtures of two single-tailed surfactants with opposite charge have been widely observed1484950515253. It is known that lipids with double hydrocarbon chains such as phospholipids have a tendency to form vesicles, i.e., liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…When diluted in aqueous solutions, cationic and anionic surfactant mixtures can form a variety of microstructures, including vesicles123, rod or worm-like micelles45678 and other bilayer lamellar phases91011. Mixtures of single-tailed SDS and single-tailed dodecyl trimethyl ammonium bromide (DTAB)12, sodium octyl sulfate (SOS) and cetyl trimethyl ammonium bromide (CTAB)3131415, are two widely investigated catanionic mixtures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipated that when the molecules were in close proximity, inherent cohesive or repulsive forces might play a dominant role, thereby leading to a time-dependent stable state. [23] At lowpressures (ca. 10 mN m À1 ), the variation was insignificant, which indicated that the monolayer was stable.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous solutions of surfactants of opposite charges, called catanionic surfactants, exhibit unique properties originating from the strong electrostatic interactions between their oppositely charged head groups. Mixtures of the anionic surfactant SDS and the cationic surfactant CTAB form mixed micelles in both SDS-rich and CTAB-rich solutions, whereas between these compositions, vesicles and formation of a 1:1 precipitate are observed [76][77][78][79]. It was shown that the correlation length of 0.24 M CTAB-SDS increases from 0.4 to 2.5 nm as the SDS content of the surfactant mixture is increased from 0 to 15 mol%, leading to increased solubility of the hydrophobic monomer C17.3M in the micellar solution [37].…”
Section: Preparation Of Hydrophobically Modified Hydrogelsmentioning
confidence: 99%